2014
DOI: 10.1007/s10664-014-9306-z
|View full text |Cite
|
Sign up to set email alerts
|

An elicitation instrument for operationalising GQM+Strategies (GQM+S-EI)

Abstract: Context: A recent approach for measurement program planning, GQM + Strategies, provides an important extension to existing approaches linking measurements and improvement activities to strategic goals and ways to achieve these goals. There is a need for instruments aiding in eliciting information from stakeholders to use GQM + Strategies. The success of GQM + Strategies highly depends on accurately identifying goals, strategies and information needs from stakeholders.Objective: The research aims at providing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Both cases are related to social activities where a team of people uses the methods introduced. The first method is a security risk analysis method (countermeasure graphs) [3], and the second an elicitation instrument to gather goals, information needs, and strategies from stakeholders to operationalize GQM+Strategies [27]. In this section we describe the action research processes and models of collaboration, while further details on the research context and actions taken can be found in [3,27].…”
Section: Action Research Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…Both cases are related to social activities where a team of people uses the methods introduced. The first method is a security risk analysis method (countermeasure graphs) [3], and the second an elicitation instrument to gather goals, information needs, and strategies from stakeholders to operationalize GQM+Strategies [27]. In this section we describe the action research processes and models of collaboration, while further details on the research context and actions taken can be found in [3,27].…”
Section: Action Research Casesmentioning
confidence: 99%
“…For example, rather than asking for the goals directly, we asked when the practitioners believe their improvement program is successful, and how the success could be achieved. The details and ratio- nales for formulating the questions in the interview guide are presented in [27]. Only one interview was conducted for improvement program A.…”
Section: Case 2: Elicitation Instrument For Gqm+ Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important that the metrics be collected be determined as early as the initial planning in order to fulfill the organization's needs [12]. There is no standard way of defining the structure, quantity, and syntax of goals and questions [25]; (iii) Insufficient cost-saving methods. Collection of data has been a critical activity due to cost concerns.…”
Section: A Research Backgroundmentioning
confidence: 99%
“…Furthermore, organizations have restricted resources to fund measurement programs. To achieve cost reduction when managing measurement programs, questions and goals could be reused, and the number of metrics limited [25]; (iv) Lack of measurement expertise. The lack of informed judgment for selecting the relevant number of metrics is another reason for unsuccessful software measurement programs.…”
Section: A Research Backgroundmentioning
confidence: 99%